Evaluation of caffeine modulation of topiramate effect on locomotor activity of zebrafish larvae in pentylenetetrazol-induced seizure model - Adrian Bartoszek; Emilia Fornal (PLoS ONE, 2025)
Epilepsy is a prevalent neurological condition marked by seizures that lead to neurobiological and behavioral impairments. Caffeine (CAF), the world’s most consumed stimulant, reportedly affects both epileptic seizures and the efficacy of antiepileptic drugs, particularly topiramate (TPM). This study aimed to investigate the effects of CAF on TPM in a pentylenetetrazol (PTZ)-induced seizure model using zebrafish larvae. Four days post-fertilization Danio rerio larvae were incubated for 18 hours with CAF, TPM, or CAF+TPM, followed by an assessment of locomotor activity. Seizures were induced by adding PTZ to achieve a final concentration of 20 mM. In the PTZ-induced seizure model, the application of CAF in doses over 50 mg/L resulted in a decrease in the average movement. TPM ( > 50 μM) significantly protected larvae against the PTZ. The addition of 15 mg/L CAF to TPM did not affect larval activity at any TPM concentration tested; however, higher doses of CAF significantly reduced larval activity. CAF doses above 25 mg/L altered the activity of larvae treated with TPM in the PTZ-induced seizure model. Larvae exhibited differential heart rate (HR) responses to CAF exposure across doses. CAF at 75 mg/L significantly increased HR, while doses of 175 mg/L and higher induced bradycardia. TPM, across all tested doses, did not independently influence HR. The study provides valuable insights into the interactions between CAF and TPM, which may inform future research on human epilepsy. However, the extrapolation of these results to other species should be approached cautiously due to physiological differences.